Volume 3: Participatory Monitoring, Evaluation, and Learning in Complex Adaptive Environments - and SACE (SACE Program, 2018)
This volume is the last in a series of papers about systems approaches in complex environments, which includes the use of the collective impact model to address large-scale social problems, and the application of participant-driven MEL techniques across 17 networks of civil society organizations. It is based on the experiences of Root Change and Chemonics, two development partners working on a USAID civic engagement project in Nigeria (2013-2018), as well as hundreds of civil society organization partners. This is the final paper in the series and aims to highlight how the adaptation of participatory monitoring, evaluation, and learning techniques (e.g., most significant change, outcome mapping, and outcome harvesting) evolved and ultimately empowered cluster members. The first paper in the series presented a brief introduction to systems approaches in advocacy settings, the SACE theory of change, and the scope of Root Change’s work as technical lead on capacity building and measurement. The second volume aims to address the innovative use of the advocacy strategy matrix, adapted from work by the Center for Evaluation Innovation, for collective impact and the Collective Impact Model, an approach that engages multiple players in working together to solve complex social problems.